Analysis of transcriptome in the relationship between expression of PRC1 protein and prognosis of patients with cholangiocarcinoma. Issue 3 (March 2021) - Wang, Qing; Lu, Shaoqiong; Chen, Ying; He, Hua; Lu, Weihui; Lin, Kanru
Objective: To investigate whether protein regulator of cytokinesis 1 ( PRC1 ), which is involved in the regulation of human carcinogenesis, contributes to poor prognosis in patients with cholangiocarcinoma (CCA). Methods: Data and tissues from patients with CCA were retrospectively studied. Immunohistochemical staining and western blotting were used to evaluate and contrast the PRC1 expression profile at the protein level in CCA tumour and pericarcinomatous tissues from the same study population. Relationships between clinical characteristics and patient survival were observed using univariate and multivariate analyses. Correlations between PRC1 expression and clinical characteristics were analysed by logistic regression. Results: A total of 45 patients were included. PRC1 expression was found to be upregulated in CCA cancer tissues versus pericarcinomatous tissues. Overexpression of PRC1 was shown to be related to tumour differentiation, tumour node metastasis staging and lymph node metastasis, and was also revealed to be an independent marker of poor CCA prognosis. Conclusions: The present results suggest that PRC1 may be a prognostic and therapeutic biomarker for patients with CCA.